Phytochemical constituents, antioxidant and antibacterial activities of methanolic extract of Ardisia elliptica - Al-Abd, N.M.; Nor, Z.M.; Mansor, M.; Zajmi, A.; Hasan, M.S.; Azhar, F.; Kassim, M. (Elsevier, 2017)
Objective To investigate the antioxidant, antibacterial, and chemical ingredients of Ardisia elliptica (A. elliptica) methanolic extracts. Methods The plant was extracted using methanol. Antibacterial and antioxidant activities were evaluated. Results The results showed that both fruit and leaf extract of A. elliptica have significant antibacterial activities against Gram-positive and Gram-negative bacteria. Fruit extracts showed higher content of phenolic (71 ± 0.03 GAE/mg extract dry weight), in comparison to the leaf extracts (37 ± 0.05 GAE/mg extract dry weight). Flavonoid content, and Fe2+ chelating activity of fruit extracts were higher than leaf extract. The percentage radical inhibition of fruit extract is found to be higher (70%) than that of leaf extract (60%). LCMS results indicated that the major compounds in the fruit extract were Gingerol, Aspidin, Kampherol, and Stercuresin, while the leaf extract contained Gingerol, Aspidin, Triangularin, and Salicyl acyl glucuronide. Furthermore, the results of GCMS indicated that fruit extract contained these major compounds: Vitamin E Tocopherol, 5-hepylresornicol, 2-Nonylmalonic acid, 5-pentadecylresornicol, and Stigmasta-7-22-dien-3-ol. However, leaf extract of A. elliptica contained these major compounds: Alpha Amyrenol, 4,4, 6, 6a, 6b, 8, 8a, 9,10, 11,12,12a, 14, 14a, 14b octadehydro-2H-picen-3-one, and Lonasterol, 4-t-Butyl-2-[4-nitrophenyl] phenol. Conclusions The results provide evidence that fruit and leaf of A. elliptica extracts might indeed be used as a potential source of effective natural antimicrobial and antioxidant agents in pharmaceutical and food industries.